CHARACTERIZING OF SKIPJACK (Katsuwonus pelamis) SUPPLY CHAIN ON POLE AND LINE FISHERY IN INDONESIA FMA 714 AND ADJACENT: A CASE STUDY IN SIKKA REGENCY, WEST NUSA TENGGARA-INDONESIA - Agustinus Anung Widodo; Lilis Sadiyah; Fayakun Satria (Indonesian Fisheries Research Journal, 2021)
In order to obtain detailed characteristic of skipjack (SKJ) supply chain on pole and line (PL) fishery operates in Indonesia Fisheries Management Area (I-FMA) 714 and its adjacent areas, Center for Fisheries Research (CFR)-MMAF with WCPFC carried out a research in Sikka Regency. Data and infomation obtained through port sampling program, observer program and stakeholders workshop. Result shows that primary actors and processes of supply chain of skipjack on PL fishery based in Sikka consisted of PL fishers (skipper and crews), collector and traders, processors and market. Total active PL boats were 67 which supported by ± 40 lift-net (bagan) to provide 300-400 tonnesnes live bait, 11 small-medium scale and 5 large scale collectors and traders, 5 small and 4 large processors and local, domestik, export market. About 3556.9 tonnes SKJ caught by PL based in Sikka in 2017, about 56% were processed as katsuwobushi (smoke fish) for being exported to Japan, 35 % were frozen processed for being exported and marketed to Europe-US and domestic market in Makassar, Bali, and Surabaya. About 9% of the total catch of PL fishery based in Sikka were locally marketed as cold-fresh SKJ.